PARASITES IN THE BODY OF ELDERLY PEOPLE - Bobojonov Islom Rustam O’g’li, Bobojonov Islom Rustam O’g’li (Actual problems and prospects of the study of the fauna, 2024)
The degree of influence of parasites in the body of adults and ways to get rid of them